An International Multilevel Analysis of Product Innovation - Lederman, Daniel (2012)
This paper studies multilevel determinants of product innovation by incumbent firms with data from 68 countries, covering over 25,000 firms in eight manufacturing sectors. The author assesses the predictions of interdisciplinary research on firm behavior in different contexts, which have emphasized that product innovation is affected by three sets of factors: the extent of global engagement, information spillovers, and market structure. The empirical model of the probability of observing a product innovation, a probit model, by a firm considers three levels of analysis: firm characteristics, industry characteristics, and the national context. The econometric evidence supports the global engagement and information spillovers hypotheses, but the evidence on the role of market structure is mixed. Regarding global engagement, the evidence suggests that product innovation by incumbent firms is positively correlated with the act of investing in R&D and licensing of foreign technologies, and country-level average import tariffs reduce the probability of product innovation. Regarding information spillovers, the evidence also shows that a country's patent density is positively correlated with product innovation. In contrast, concerning the market structure hypotheses, country-level indicators of business density and of policy-induced costs of entry are not robustly correlated with product innovation.